Implementation of Policies to Improve Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019 - Sarese, Djemy; Mokat, Jetty; Kairupan, Sisca B. (Technium Social Sciences Journal, 2022)
To anticipate the spread of the Covid-19 virus in Indonesia, various efforts have been made by the central and regional governments. Tomohon City is the first area in North Sulawesi to have a regional regulation to enforce compliance with the Covid-19 prevention health protocol. This study aims to determine and analyze how the implementation of the Tomohon City Regional Regulation No. 1 of 2021 concerning Improvement of Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019 in terms of 3 indicators, namely Health Protocols, Supervision, and Imposition of Sanctions. The research method used is a qualitative method with data collection techniques in the form of observation, interviews, documentation and literature studies. The research location is Tomohon City, North Sulawesi with a total sample of 8 people consisting of the government and the community. The results of the study show that 1) The application of the health protocol as stipulated in Article 8 has not run optimally due to the lack of public awareness and discipline; 2) Supervision as stipulated in article 13, namely regarding the monitoring, prevention and clarification of fake news, periodic evaluation and acceptance of public complaints has been running effectively; and, 3) The imposition of sanctions as stipulated in Article 23 has not been implemented effectively. This is due to the lack of firmness of the officers in the field.